Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. **There will be no changes to other Yahoo properties or services, or your Yahoo account.** You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

## Trending News

# How do you simplify z^-2 / z^-3?

At this point it's confirmed that I suck at math.

### 21 Answers

- ?Lv 71 month ago
Since the base is the same just subtract the exponents.

A negative exponent means you have a fraction

Go back to the method you used when dividing a common fraction by a common fraction

z^-2 = 1 / z^2

z^-3 = 1 / z ^3

Do you remember the rule: invert and multiply?

[1 / z^2] / [1 / z^3] = [1 / z^2] X [z^3 / 1]

- ?Lv 71 month ago
In a a ratio, if the bases are the same, subtract the exponents.

(-2) - (-3) = 1 therefore z to the first power. QED

- How do you think about the answers? You can sign in to vote the answer.
- JimLv 71 month ago
First, invert both to get rid of negative exponents:

z⁻²/z⁻³ = z³/z²

Now reduce: (z²/z²)*z¹ = 1*z

= z

- RaymondLv 71 month ago
Go back to law of exponents:

When multiplying two powers of the same base (here, the base is "z"), just add the powers.

example: z^2 * z^4 = zz * zzzz = zzzzzz = z^6

z^2 * x^4 = z^(2+4) = z^6

When dividing two powers (of the same base), subtract the powers

z^5 / z^2 = zzzzz / zz = zz*zzz / zz = zzz = z^3

z^5 / z^2 = z^(5-2) = z^3

z^0 = 1

This comes from the second rule.

Anything divided by itself = 1

z^4 / z^4 = 1

z^4 / z^4 = z^(4-4) = z^0

A negative power is a "reciprocal" (a fraction)

1 / z^3 = z^0 / z^3 = z^(0-3) = z^(-3)

-----

Your problem begins as a case for the second rule (division)

just be careful with signs

z^(-2) / z^(-3) = z^(-2 - -3) = z^(-2+3) = z^1 = z

- lenpol7Lv 71 month ago
Remember z^-2 = 1/z^2

Similarly z^-3 = 1/z^3

Hence [ 1/z^2]/ [1/z^3] is division of fractions.

Hence

[1/z^2] x [z^3/1]

Cancel down by 'z^2'

Hence

1/1 x z/1 = 'z^1' = 'z' The answer

- PopeLv 71 month ago
Hardly anyone gets these right. Try multiplying numerator and denominator both by z³, but do be careful.

z⁻² / z⁻³

= (z⁻² / z⁻³)(z³ / z³) ... where z ≠ 0

= z³⁻² / z³⁻³

= z¹ / z⁰

= z

z⁻² / z⁻³ = z, where z ≠ 0

Without that exclusion, the answer z would be incorrect, or at least incomplete. In the first step, the denominator is multiplied by z³. If z were zero, that would be division by zero, an invalid operation. The given expression is undefined at z = 0. No amount of simplification can change that.

- PuzzlingLv 71 month ago
When you have a negative exponent, you can swap it to the other side of the fraction and change the sign. So z^-2 would change to z^2 in the denominator. Likewise, z^-3 in the denominator would become z^3 in the numerator.

So this would turn into:

z^3 / z^2

At that point you can reduce this. When you divide two numbers (with the same base), you subtract the exponents:

= z^(3-2)

= z^1

= z

Answer:

z (as long as z ≠ 0)